2020
DOI: 10.35925/j.multi.2020.3.26
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency comparison of Python and RapidMiner

Abstract: Machine learning is an important technique that helps companies, institutes, and humans to improve the quality of decision making. As there are many different free tools on the Internet for machine learning, we need comparisons, benchmarks to provide help in the selection of the appropriate analysis technique. This paper aims at providing a comparative study of the two most powerful and opensource machine learning tools Python and RapidMiner by using most common supervised machine learning techniques Decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…The collected data was verified, and any missing data was obtained from the project websites. The retrieved data were then analyzed through RapidMiner, a software recommended by László and Ghous (2020) for its high accuracy in data analysis. In total, seven models were analyzed, including: (1) Decision Tree (DT), (2) Random Forest (RF), (3) Gradient Boosted Tree (GBT), ( 4) an Ensemble Classifier of DT and RF, (5) an Ensemble Classifier of DT and GBT, (6) an Ensemble Classifier of RF and GBT, and ( 7) an Ensemble Classifier of DT, RF, and GBT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected data was verified, and any missing data was obtained from the project websites. The retrieved data were then analyzed through RapidMiner, a software recommended by László and Ghous (2020) for its high accuracy in data analysis. In total, seven models were analyzed, including: (1) Decision Tree (DT), (2) Random Forest (RF), (3) Gradient Boosted Tree (GBT), ( 4) an Ensemble Classifier of DT and RF, (5) an Ensemble Classifier of DT and GBT, (6) an Ensemble Classifier of RF and GBT, and ( 7) an Ensemble Classifier of DT, RF, and GBT.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with the findings of Ngoendee and Charoenruengkit (2021), who determined that the use of an ensemble model was the most effective and precise approach in data mining. The study by László and Ghous (2020) also concluded that the utilization of model integration techniques is an appropriate method for combining multiple models to obtain the most accurate and optimal predictions.…”
Section: Machine Learning Techniquementioning
confidence: 99%
“…Berbeda dari penelitian yang dikaji sebelumnya, penelitian ini melakukan klastering [11] menggunakan data penyakit tertinggi di RSUD Kota Bandung dengan berbagai kelompok usia yang kemudian diolah menggunakan algoritma K-Means. Pengolahan data menggunakan tahapan standard CRISP-DM (Cross-Industry Standard Process for Data mining) yang dilakukan dengan menggunakan perangkat lunak RapidMiner 9.10 [12], Microsoft Excel dan Bahasa pemrograman python dengan library Scikit-Learn [13] dalam pengolahannya.…”
Section: Pendahuluanunclassified
“…This software was developed by Ralf Klinkenberg, Ingo Mierswa, and Simon Fischer (Pynam et al, 2018). RapidMiner requires a shorter processing time than other machine learning software (Faid et al, 2019;László & Ghous, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One of the machine learning algorithms that shows superior performance in various research is the Random Forest proposed by Breiman (László & Ghous, 2020). This algorithm is a development of a decision tree (Hadiprakoso et al, 2022) that combines bootstrap aggregating (bagging) and random feature selection methods (Mantri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%